Observation of room-temperature out-of-plane switchable electric polarization in supported 3R-MoS₂ monolayers - Ma, Li (2024)
Two-dimensional (2D) ferroelectrics have attracted considerable attention due to their potential in the development of devices of miniaturization and multifunction. Although several van der Waals (vdW)-layered materials show ferroelectricity, the experimental demonstrations of ferroelectric behavior in monolayers are very limited. Here we report the observation of room-temperature out-of-plane switchable electric polarization in supported MoS2 monolayers exfoliated from 3R-stacked bulk crystals under ambient conditions. Using in situ piezoelectric force microscopy and Kelvin probe force microscopy in a glovebox, we reveal that trapped water/ice molecules are responsible for this switchable electric polarization and this conclusion is strongly supported by theoretical simulations. It is worth noting that the water/ice trapping in the monolayers exfoliated from 2H-stacked MoS2 crystals is not as much as that in 3R monolayers and, consequently, the out-of-plane electric polarization is missing there. Our findings indicate that monolayers with a trapped single layer of polar molecules might be emerging alternatives to 2D ferroelectrics. Furthermore, the stacking sequences may bring new properties and applications to 2D vdW materials not only when we stack them up but also when we thin them down.